Secrets of intellectual property : a guide for small and medium-sized exporters (ITC/WIPO GenevaCH, 2004)
Presents a guide on intellectual property issues for the benefit of all SME policy makers, SME support and finance institutions, SME training and teaching institutions and SMEs.
Keywords: INTELLECTUAL PROPERTY